Students’ Readiness for Learning English Through Blended Learning at SMP N 5 Padang - Hasanah, Filza; Imelwaty, Sri; Sevrika, Hevriani (Jurnal Pendidikan Tambusai, 2021)
The purpose of this research wants to find out the students’ readiness for learning English through blended learning. This research was conducted using quantitative research with a survey method. The population of this research is the 8th grade students at one of junior high schools in Padang, West Sumatra with 250 numbers of students. This study used a total sampling, but only 50 % (125 students) of the students filled out the questionnaire. The online questionnaire using Google form was used and distributed to the students. The results of this study show that the tendency of quite high percentage of the six aspects of student readiness, namely classroom learning, online learning, online interaction, technology, learning flexibility and learning management. These indicate that the junior high school students are ready to learn English by using blended learning